La natación como medio de mejoramiento de la condición física en niños y niñas con capacidades especiales en la unidad educativa Manuel Gonzalo Albán r. durante el periodo 2014-2015 - Molina Saragosin, Edgar Iván (2015)
The research it was carried out in the Manuel Gonzalo Albán R. High School in order to elaborate a swimming guide for children with special capacities because nowadays the physical education has a pioneer suggestion to improve the quality life of these children. For that reason, the realization of this investigation, using different techniques for the boy's physical development. So it puts in consideration the present swimming guide for children with special capacities in this Institution, which is the most importante because through we can improve the lifestyle and the boy's physical condition, through improvement of their own abilities and skills in the swimming field….